Implications of the Weibull K Factor in Resource Assessment - Thamhain, Mathias (2012)
This study investigates the implication of the site specific wind speed distribution on the energy production of a wind turbine generator. It will proof that the average wind speed and the power density are not a good measure on how well a turbine will perform; the performance depends on how well a power curve corresponds to the wind speed distribution. The Weibull distribution is commonly used to describe the probability distribution of wind speed at a given location. Two parameters, the scale factor (c, also sometimes referred to as A) and the shape factor (k) are sufficient to describe a curve which approximates the probability distribution of the wind speed.The Rayleigh distribution (defined as a Weibull distribution with the shape factor k = 2), is considered frequently as a reference frequency distribution. EAPC ́s practical experience in wind resource assessment in Southern Latin America has revealed a broad variety of shape factors beyond the standard k=2. We have also found that for a given mean wind speed, different shape factors lead to different magnitude of annual energy production on the other. This is especially the case for high wind speeds, where impact on annual energy production can be 15% or higher.